Abnormal leptin bioavailability in adolescent idiopathic scoliosis: an important new finding - Liu, Zhen; Tam, Elisa M S; Sun, Guang-Quan; Lam, Tsz-Ping; Zhu, Ze-Zheng; Sun, Xu; Lee, Kwong-Man; Ng, Tzi-Bun; Qiu, Yong; Cheng, Jack C Y; Yeung, Hiu-Yan (Spine (Philadelphia, Pa. 1976), 2012)
This was a cross-sectional study. The present study aimed to explore the differences in leptin bioavailability between adolescent idiopathic scoliosis (AIS) and healthy age-matched girls in a Chinese Han population. AIS is a common spinal deformity mainly occurring in girls during the peripubertal period. The development of scoliosis is related to relative anterior spinal overgrowth. AIS girls also have associated lower body mass index (BMI) and lower bone mineral status. Leptin, together with soluble leptin receptor (sOB-R), was shown to play an important role in the regulation of bone and energy metabolism in children. It was hypothesized that leptin and sOB-R are abnormal and associated with deranged growth and anthropometric phenotypes in AIS girls. Serum leptin and sOB-R were measured together with documentation of anthropometric parameters and clinical data in 95 AIS girls and 46 healthy matched controls (age 11-16 years). Serum leptin and sOB-R concentrations were measured by enzyme-linked immunosorbent assay and correlated with the different measured parameters. AIS girls had significantly lower BMI and longer arm span than healthy controls. AIS girls were found to have significantly higher sOB-R levels and lower free leptin index (FLI) after adjusting for age and body weight in multivariate regression analysis. Significant correlation was found between sOB-R, FLI, and curve severity in AIS girls. This is the first study demonstrating the presence of abnormal leptin bioavailability in AIS girls that might play an important role in the etiopathogenesis of AIS. Further investigation is required to provide a better understanding of the underlying mechanisms, with the aim to explore the potential clinical application as a biomarker for predicting curve initiation or progression in AIS.